Analysis of the influence of transgenic kalanchoe extract with cecropin P1 on the state of a non-infected wound in rats - Belous Alexandr (EDP Sciences, 2021)
In this article data on the analysis of the effect of transgenic Kalanchoe pinnate extract with cecropin P1 on the state of uninfected wounds in rats are presented. The study used Wistar rats weighing 220 ± 20 g. A wound of 20 × 20 mm was modeled under anesthesia in sterile conditions. The wound was treated during 14 days with the 3% hydrogen peroxide solution in all experimental groups. Additional treatment with the 10% cefazolin solution was used in group No. 2; with Kalanchoe juice it was used in group No. 3, and with transgenic Kalanchoe extract cecropin P1 it was used in group No. 4. The effectiveness of the treatment of the wound process was evaluated by the external state of the wound and planimetry indicators. It was found that all analyzed parameters of the experimental groups were better than in the control group of animals. However, the effect was most pronounced in the group treated by transgenic Kalanchoe extract with cecropin P1, The results of the study allow us to recommend further preclinical study of the substance for the possible treatment of trophic ulcers in patients with diabetes mellitus.